ANXIETY LEVEL ANALYSIS OF NURSING STUDENT WHO TOOK OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) USING FACE TEMPERATURE DISTRIBUTION BASED ON THERMAL IMAGING - Ni Made Dian Sulistiowati; Wayan Nata Septiadi; Luh Putu Nopriani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Background and Purpose: The condition that a person experiences stress can affect the function of various organ systems of the body, especially the cardiovascular system. Manifestations of prolonged stress can turn into anxiety. This study aims to determine differences in temperature distribution in the face of students who experience anxiety facing the OSCE.Method: This research method using pre-experimental design where samples are experiencing anxiety seen temperature distribution in the face area by using thermal imaging. The sample was selected using total sampling technique in which as many as 81 students were undergoing tests OSCE is used as a sample in this study. The instrument used to measure the level of anxiety is the GAD 7, consists of seven items given questions prior to the measurement of temperature using thermal imaging.Results: The results obtained are subjected to mild anxiety as much as 49 respondents where the frontal head temperature measurement that 23 people was febrile, 22 people was normal and 4 people was hypothermia. While the results of the temporal head measurement that 27 people was febrile, 20 people was normal, and 2 people was hypothermia.Conclusion and recommendation: There is a difference in temperature at each level of anxiety as measured by the temperature of the temporal and frontal. Therefore, it needs to be investigated further there a change in temperature by measuring themal imaging, after the addition of interventions for coping with anxiety.